5. Cerebellar direct current stimulation modulates pain perception and its neural correlates in humans. Issue 12 (December 2016) - Bocci, T.; Santarcangelo, E.; Parenti, L.; Barloscio, D.; Carli, G.; Ferrucci, R.; Priori, A.; Valeriani, M.; Sartucci, F.
Abstract : The cerebellum is involved in a number of integrative functions, but its role in pain perception and nociceptive processing is poorly understood. We evaluated the effects of transcranial cerebellar direct current stimulation (tcDCS) by studying changes in perceptive threshold (PT), pain intensity (VAS) and laser evoked potentials (LEPs). Twenty-five subjects were studied before and after anodal, cathodal and sham tcDCS. LEPs were obtained using a Nd:YAP laser. VAS was evaluated by delivering laser pulses at two different intensities, respectively two and three times the PT. Cathodal polarization dampened the perceptive threshold and increased the VAS score, while anodal one had opposite effects (p  <  0.001, two-way repeated measures ANOVA, "time" × "stimulation"). Cathodal tcDCS increased LEPs amplitudes and decreased their latencies, whereas anodal polarization elicited opposite effects (p  <  0.0001). Motor thresholds assessed through transcranial magnetic stimulation were not affected by tcDCS. tcDCS modulates pain perception and its cortical correlates. As it is effective on N1 and N2/P2 components, we speculate that the cerebellum modulates the activity of both somatosensory and cingulate cortices, thus interfering with the sensory-discriminative and affective-emotional dimensions of pain. Our findings prompt investigation of the tsDCS as a novel and safe therapeutic tool in pain syndromes.